The history of Hui Muslim minority in Ming Dynasty : a social and cultural study - Ji, Sakeenah Shan Shan (International Institute of Islamic Thought and Civilization,International Islamic University Malaysia, 2010)
The history of Islam in China could be viewed over five dynasties namely Tang, Song, Yuan, Ming and Qing dynasty. The Yuan Dynasty was considered as the Golden Age of Islam in China. However this thesis focuses on the development of Islam in the Ming Dynasty. Islam in Ming dynasty went through a process of adjustment and adaptation. The term 'Hui' was coined in this era. The assimilation process took place by Emperor's decree because he no longer wanted to see the Chinese divided into different groups. As a result Muslims who were mostly descendents of Middle East origins gradually with Chinese society and started to live and practice Chinese culture but still had a strong understanding of Islamic teachings. By this time, their identities were hardly distinguishable from the Han majority. In other words, social interaction was at a peak during this era. Besides that, they were given full freedom to fulfill duties as Muslims. Mosques were built in high-populated areas like Nanjing and Xinjiang. Islamic arts and literature continued to grow. Indeed, it obviously showed the continuation of the glorious era of Yuan in its own way. Therefore this research will be an effort to explore the conditions of Islam in Ming and how it impacted the history of Islam in China.